A novel chromatographic separation method for rapid enrichment and isolation of novel flavonoid glycosides from Sphaerophysa salsula. Issue 21 (13th October 2020) - Wang, Weidong; Dang, Jun; Shao, Yun; Jiang, Lei; Liu, Zenggen; Mei, Lijuan; Tao, Yanduo
Abstract: Flavonoid glycosides exist widely in medicine herbs and often used as nutraceuticals because of their excellent bioactivity and low toxicity. For accurate quality control and bioactivity assessment of Sphaerophysa salsula, a rapid and productive method to isolate flavonoid glycosides is needed. Therefore, this work reports the development of a novel comprehensive strategy based on an online middle‐pressure chromatography and preparative high‐performance liquid chromatography for rapid enrichment and separation of flavonoid glycosides from S. salsula . First, the flavonoid glycosides were enriched using an online middle‐pressure chromatographic column containing stationary middle chromatogram isolated phase. During this process, the high‐volume injection of the extracting solution was realized by an empty precolumn positioned before the main chromatographic tower. Then, the compounds were separated through preparative high‐performance liquid chromatography with Megress C18. As a result, one new flavonol 3‐O‐glycoside (2 ) and two known flavonol 3‐O‐glycosides (1, 3 ) were targetedly isolated from S. salsula . The content of compounds 1–3 in S. salsula was 0.09, 0.11, and 0.18 wt%, respectively. Comparing to traditional enrichment and separation methods, our technique offers significantly shorter sample pretreatment time as well as high reproducibility. We believe that our separation method has a strong potential to be used for the processing of other medicinal plants.